MEDIA STIMULI OF EMOTION RECOGNITION: A STATE-OF-THE-ART REVIEW OF CURRENT TRENDS AND TECHNOLOGY - Hariyady H.; Ibrahim A.A.A.; Teo J.; Weng N.G.; Ahmad A.; Yassin F.M.; Salimun C. (Scientific Research Support Fund of Jordan, 2024)
Emotion identification has received a lot of interest in recent years, with applications in mental health, education and marketing. This systematic literature review aimed to provide an up-to-date overview of trends and technological advancements in the use of media stimuli for emotion recognition. A comprehensive search yielded 720 relevant studies from 2018 to 2023, which employed various media stimuli to induce and measure emotional responses. The main findings indicate that audios and videos are the most used media stimuli for emotion recognition. However, there is a growing trend toward exploring other forms of media, such as physiological signals and wearables. This review highlights the varying ecological validity of different stimulus types and emphasizes the potential of virtual reality for more objective emotion recognition. These findings offer valuable insights for future research and practical applications in the field by synthesizing knowledge to inform advancements in media stimuli for emotion recognition. 2023, Scientific Research Support Fund of Jordan. All rights reserved.